8 practice tests for reading and math, grades 7-8 - Priestley, Michael (New York : Scholastic, 2002)
Presents eight practice tests for seventh and eighth graders in reading and math, designed to help students prepare for state and national standardized tests, and includes answer keys, an index of tested skills, and test-taking tips.
"Grades 7-8"--Cover.
"Great practice for the MAT, CTBS TerraNova, CAT, Stanford, and more!"--Cover.
Professional
Keywords: Mathematics -- Study and teaching; Reading; Teaching -- Aids and devices; Mathematics -- Study and teaching; Reading; Teaching -- Aids and devices